BO‘LAJAK YO‘L MUHANDISLARINING KASBIY KOMPETENSIYALARINI RIVOJLANTIRISH DASTURIY TA’MINOTINI TAKOMILLASHTIRISH MODELI - Toreshov, D.B. (SCIENCE and SOCIETY, 2024)
The article presents a software improvement model aimed at developing professional competencies of future road engineers. In the conditions of the rapid development of technologies and changing requirements for educational programs, it is important to ensure the high qualification of specialists in the field of road construction and management.
Keywords: road engineers; professional competencies; educational model; software; development of professional skills